Enhanced selective recovery of selenium from anode slime using MnO2 in dilute H2SO4 solution as oxidant. (1st February 2019) - Xiao, Li; Wang, Yongliang; Yu, Yang; Fu, Guoyan; Liu, Ya; Sun, Zhi; Ye, Shufeng
Abstract: As important rare raw material, Se and its compounds are widely used in metallurgy, glass manufacturing, chemicals and pigments, and electronics industry. However, current processes used for Se recovery are usually constrained by the serious pollution and high energy consumption. To dispose the issues in the process of Se recovery, this study developed an environmentally friendly process by using MnO2 in dilute H2 SO4 as oxidant to efficiently recover Se and Cu. The effects of MnO2 dosage, H2 SO4 concentrations, stirring speeds and temperature on the recovery were investigated. It was found that the major Se bearing phases in anode slime were elemental Se and Ag2 Se. The oxidation capacity of MnO2 greatly increased with the H2 SO4 concentration higher than 0.5 M and at a temperature above 60 °C. Optimum conditions derived from this study were 1.2 g MnO2 dosage, 1.0 M H2 SO4, 600 rpm, and temperature at 80 °C, under which both the Se and Cu were recovered by 100% after 6 h. The cost-benefit analysis of the proposed process manifested that the profit of processing 1 t of anode slime was $ 82, and the sensitivity analysis showed that the price of Cu2 Se and the Se recovery rate were the most important determinants of the profit. This research has great potential in Se recovery from anode slime. Graphical abstract: Image 1 Highlights: A novel process for selenium recovery from anode slime is proposed. Se and Ag2 Se are the major selenium components in anode slime. MnO2 is effective for the conversion of selenide to selenite. The H2 SO4, temperature and stirring have great impact on selenium recovery.